A preliminary list of the subfamily Cerambycinae (Coleoptera: Cerambycidae) of Vietnam - Nga, Cao Thi; Long, Khuat Dang (Academia Journal of Biology, 2014)
Most species of the longhorned beetles are known to damage living trees and attack dead trees or fallen logs and are of economic importance because their woodboring larvae are destructive to plants and freshly cut logs. The paper presented a checlist of publising species of Vietnam longhorn beetle fauna of the subfamily Cerambycinae with local and world distribution provided. Of the total of 259 cerambycid species belonging to 88 genera and 18 tribes, seven diverse tribes are Clytini (74 species), Callichromini (41 species), Cerambycini (35 species), Molorchini (19 species), Callidiopini (18 species), Methiini (13 species) and Cleomenini (11 species).